Are gold and bitcoin a safe haven for European indices? - Nikola Fabris; Milutin Ješić (Journal of Central Banking Theory and Practice, 2023)
Numerous turbulent events in the recent past have raised the issue of an asset that could play the role of safe haven. Although for many years it was considered that gold has the role of a safe haven, an increasing number of recent works challenge such a point of view. The emergence of cryptocurrencies after the Global financial crisis has opened up numerous questions, one of them being whether cryptocurrencies, as an asset (money) independent of governments, can play the role of safe haven. Therefore, the paper examines whether gold and bitcoin, the latter as the best representative of cryptocurrencies, can play the role of safe haven in relation to European indices. In the paper, this hypothesis was confirmed for gold and rejected for bitcoin.
Keywords: C58; G11; 330; Safe Haven; Gold; Bitcoin; European indices